Gateway Positioning in Flying Networks - Hugo Daniel Teixeira Rodrigues (2020)
Over the past few years the usage of Unmanned Aerial Vehicles (UAVs) for a myriad of applications, both civil and military, has increased. As they present capability to operate in virtually anywhere, the ability to hover over the ground, and their increasing capacity to carry cargo, has made them perfect platforms for the transport of on board communications nodes.There has been an increasing interest in UAVs in the context of Flying Networks (FNs), either to establish communication networks or reinforce telecommunications infrastructures and enable the broadband access to the Internet in Temporary Crowded Events (TCEs). However, the high mobility inherent to UAVs leads to frequent changes in the network topology, which in turn may cause connection disruptions between the UAVs, increasing the difficulty of meeting the Quality of Service (QoS) expected by the network's users.An additional problem that raises with the implementation of FNs is the total amount of time that UAVs can remain operational, as they have batteries with limited capacity, whose energy can be drained quite quickly, as it is required for both communications and movement.To connect the FN to the Internet a Gateway (GW) is required, and it can be implemented in a UAV. Thus, it is important to ensure the optimal placement of the GW UAV in order to achieve maximum network performance. In the literature, some solutions have been proposed for the placement of the UAVs that act as Access Points (APs); however, the issue of the GW UAV placement has not been studied with the desired depth. As the overall network performance can be improved if the GW UAV remains operational for the maximum amount of time, the development of an energy efficiency-aware a placement solution of the GW UAV, in order to maximize the network performance is the scope dissertation.This dissertation will focus on the issue of an energy-efficient placement of the GW UAV while maintaining coverage for the remaining nodes of the network. To tackle this issue an algorithm to the non-stationary placement of the GW UAV will be developed.